RE-EVALUATING ACCOUNTING CONSERVATISM AND ITS IMPACT ON TAX EVASION STRATEGIES: EVIDENCE FROM DISCLOSURE AND TRANSPARENCY - Arshed Makki Rashed (Scholar Express Journals, 2026)
This research study aims to test the relation between accounting conservatism and tax evasion among Iraqi non-financial firms and the moderating effect of transparency and information disclosure.
Keywords: accounting conservatism; transparency; moderation